بررسی تأثیر توانمندسازی کارکنان بر انکشاف پایدار (مطالعه موردی: پوهنتون‌های ولایت فراه) - معین پوهنوال محمد ناصر; عادلی پوهنیار عبدالرحمن; عابدی پوهنمل نورالله (Farah Research and Scientific Journal, 2025)
Sustainable development is a multidimensional and strategic concept that requires coordination among human, social, economic, and environmental factors for its realization. One of the key components in this process is employee empowerment, which, as an effective tool of human resource management, enhances efficiency, increases organizational commitment, and facilitates the achievement of developmental goals. The relationship between empowerment and sustainable development lies in the fact that empowerment strengthens human capital and enhances the capacity of organizations and communities to respond to the challenges of sustainable development. The aim of this study is to examine the impact of employee empowerment on sustainable development in the universities of Farah province. The research method is descriptive–analytical and applied in nature. The statistical population includes 208 members of the academic and administrative staff of Farah province universities (177 from Farah Emirate University and 31 from Ghurjestan Private University). Simple random sampling was used, and based on Cochran’s formula with a 5% margin of error, the sample size was determined to be 135 participants. Data were collected through a questionnaire and analyzed using the Structural Equation Modeling (SEM) approach in AMOS software. The results showed that the regression coefficient between employee empowerment and sustainable development was 0.54, indicating a positive and significant relationship between the two variables. Moreover, the components of empowerment—sense of competence (0.23), autonomy (0.09), impact (0.10), and meaningfulness (0.13)—each played an important role in enhancing sustainable development. Accordingly, employee empowerment has a significant and positive effect on the sustainable development of the universities in Farah province.